Le street art comme micro-politique de l’espace public : entre « artivisme » et coopératisme - Thomas Riffaud; Robin Recours (Cahiers de Narratologie)
Following a comprehensive approach, this study attempts to analyse the micro-politic aspects of the street art world. The data were collected from 18 artists, in participant observations and individual interviews. Results indicate that this artistic practice oscillates between « artivism » and cooperation. If many street artists strongly challenge the norms of the modern cities, others participate more or less directly to their strengthening. According to the authors, decision makers, artists, and researchers should take into account this hybridization.